Letter to Jane Tolmach from Wm. C. O'Donnell - Wm. C. O'Donnell:::::: (1970)
In this December 7, 1970 letter, Wm. C. O'Donnell, District Administrator for Congressman Chet Holifield, informs Jane Tolmach that he has enclosed a list of women who were very active in the 19th Congressional District to be considered for the Key Women recognition. He notes uncertainty about how extensive the list should be and expresses hope that the submitted names will be suitable. The second page includes a map outlining the boundaries of the 19th Congressional District in Los Angeles County.